Cultural Expertise, Law, and Rights : A Comprehensive Guide. - Holden, Livia (Milton : Taylor & Francis Group, 2023)
This book introduces readers to the theory and practice of cultural expertise in the resolution of conflicts and the claim of rights in diverse societies and cross-cultural disputes.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2023. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Electronic books